Mothers-Citizens. On the Relations Between Motherhood, Patriotism and National Consciousness by the Example of the Works by Franciszek Dionizy Kniaźnin, Józef Morelowski and Adam Mickiewicz - Kusz, Sara Anna (Papers in Literature, 2020)
The relation between Kniaźnin’s works (Matka Spartanka and Matka obywatelka) and Mickiewicz’s poem Do matki Polki is sometimes portrayed as merely the transmission of themes and motifs. This paper argues that it is more complicated than it seems. Although similarities are noticeable, these works are not comparable, since both authors wrote in completely different historical circumstances. The context discussed in this paper is the issue of national consciousness. The land as well as the state were treated as necessary conditions for the existence of the nation during Kniaźnin’s times, which is confirmed in legal textbooks, dictionaries and literature. However, these factors were no longer valid during the Romantic period. In this sense, it is Tren IV by Józef Morelowski, written in 1795, when the Third (last) Partition of Poland took place, that may be considered a representative example. Women were advised not to give birth anymore, for their children could not be Poles but Prussians or Muscovites. After such a suggestion, a revolution in the consciousness of the society was necessary in order to persuade mothers to raise their children in a patriotic manner.